1984
DOI: 10.1128/jvi.52.1.293-297.1984
|View full text |Cite
|
Sign up to set email alerts
|

Three major glycoprotein genes of varicella-zoster virus whose products have neutralization epitopes

Abstract: Varicella-zoster virus (VZV) codes for approximately eight glycosylated polypeptides in infected cell cultures and in virions. To determine the number of serologically distinct glycoprotein gene products encoded by VZV, we have developed murine monoclonal antibodies to purified virions. Of 10 monoclonal antibodies which can immunoprecipitate intracellular VZV antigens and virion glycoproteins, 1 (termed gA) reacted with gp105, 1 (termed gB) reacted with gp115 (intracellular only), gp62, and gp57, and 8 (termed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…Interestingly, a previous study by these authors showed that the smaller form of gE is present on cell surface, recycles through the endocytotic pathway, and is incorporated into virions [28]. Studies from other groups also showed that a mixture of forms of gE ranging from ,50-100 kDa are present in purified virions [29,30,31]. Therefore, the 73 kDa form of gE is present in virions where it may interact with IDE.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, a previous study by these authors showed that the smaller form of gE is present on cell surface, recycles through the endocytotic pathway, and is incorporated into virions [28]. Studies from other groups also showed that a mixture of forms of gE ranging from ,50-100 kDa are present in purified virions [29,30,31]. Therefore, the 73 kDa form of gE is present in virions where it may interact with IDE.…”
Section: Discussionmentioning
confidence: 93%
“…were scraped from minimal lactose plates into SDSpolyacrylamide gel sample buffer, boiled, electrophoresed, transferred to nitrocellulose, and reacted with antibodies as previously described (15). Rabbit anti-beta-galactosidase antiserum (a gift from V. Larson) was prepared to E. coli beta-galactosidase (Sigma catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…G-6008). The source of other ascites fluids, convalescent zoster serum, and normal human serum has been previously described (15). Southern blots.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations